IMPLEMENTATION OF THE PAUD-SD TRANSITION IS ENJOYABLE FROM THE PERSPECTIVE OF PAUD AND ELEMENTARY SCHOOL EDUCATORS IN WEST SUMATERA - Kusuma, Tesya Cahyani Kusuma; Hartati, Sofia (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to identify and analyze the implementation of a pleasant PAUD-SD transition. The type of research used is descriptive qualitative, which provides an in-depth description of the transition process from Early Childhood Education (ECE) to Primary School (SD) in the context of the understanding of ECE and SD educators in West Sumatra. The data collection method was conducted through a survey distributed using Google Form. In addition, literature review was used to enrich the analysis and provide a strong theoretical foundation. The results show that a pleasant transition is characterized by interactive and interesting activities, adequate emotional support from teachers and parents, and a learning environment that supports children's development. The findings are expected to serve as a reference for educators and policy makers in designing effective and enjoyable transition programs for children. The active involvement of parents in the transition process is crucial to ensure children feel comfortable and motivated in the new learning environment. The research emphasizes that synergy between educators, parents and the school environment is critical to creating a positive transition experience. The implementation of appropriate strategies to facilitate this transition is expected to improve children's readiness to face the challenges of higher levels of education and promote their optimal holistic development. Thus, the results of this study not only provide practical guidance but also strengthen the relevant theoretical basis in the context of educational transitions.